Ternak Ayam Ras Petelur Ditengah Pemukiman Masyarakat Dalam Perspektif Etika Bisnis Islam (Studi Kasus Di Kampung Setia Negara Baradatuway Kanan) - Badrun (Falah: Jurnal Hukum Ekonomi Syariah, 2021)
The business of laying hens is a business that has been developed by many breeders. This business has good prospects considering the high market demand and has high nutritional value and affordable prices. However, as time goes by, livestock businessmen have started to ignore the surrounding environmental conditions, in running a livestock business, of course, they must know the provisions that apply in doing business and know the procedures for doing business in accordance with the principles of business ethics. Like the chicken farm in Kampung Setia Negara Baradatu Way Kanan which was established in the middle of a community settlement, it is known that the livestock business has a negative impact on the surrounding environment. The impact is in the form of chicken manure waste.    This study aims to find out how the Islamic Business Ethics review of the chicken farming business in the midst of the Community Settlement in Kampung Setia Negara Baradatu Way Kanan by paying attention to the principles of Islamic business ethics. In doing business, of course, there are conditions before starting a business, and in running a business a businessman must of course pay attention to the environment around the business. This study uses data collection techniques with interviews conducted on chicken farm owners and the community around the farm .             Based on the results of this study, it shows that: (1) the chicken farm owned by Mr. TN in Kampung Setia Negara Baradatu Way Kanan is not in accordance with the principles of Islamic business ethics in doing business. (2) because the community around the livestock business feels disturbed by the waste generated from the livestock business in the form of chicken manure waste